THE RELATIONSHIP BETWEEN BODY FLEXIBILITY AND OVERHEAD PASSING ACCURACY IN VOLLEYBALL AMONG GRADE XI STUDENTS OF SMK NEGERI 4 KUTACANE - Habi Misfah; Orbit Irwansyah; Ladipin (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This correlational study investigates the relationship between body flexibility and the accuracy of overhead passing in volleyball. The research was conducted on a population and sample of 12 Grade XI students from SMK Negeri 4 Kutacane, selected via total sampling. Body flexibility was quantitatively measured using the standard Sit and Reach test, which primarily assesses the flexibility of the lower back and hamstring muscles. Overhead passing accuracy was evaluated through a targeted passing test, where students aimed to pass the ball accurately to a designated target area. Data analysis commenced with a Shapiro-Wilk normality test to confirm the data's parametric nature, followed by a Pearson Product-Moment correlation analysis. The results revealed a very strong, positive, and statistically significant correlation between the two variables (r = 0.872, p = 0.000). This finding indicates that higher levels of body flexibility are strongly associated with greater accuracy in performing overhead passes in volleyball. The discussion posits that enhanced flexibility allows for better body control, a wider range of motion, and more precise upper-body positioning, all of which are critical for effective overhead passing. Consequently, the study strongly recommends incorporating systematic and regular flexibility training, focusing on the lower back, hamstrings, and shoulder girdle, into volleyball training regimens for novice players to fundamentally improve their technical skills.